2010
DOI: 10.1177/0011000010378610
|View full text |Cite
|
Sign up to set email alerts
|

How Graduate-Level Preparation Influences the Effectiveness of School Leaders: A Comparison of the Outcomes of Exemplary and Conventional Leadership Preparation Programs for Principals

Abstract: Purpose: This study attempted to determine the influence of exemplary leadership preparation on what principals learn about leadership, their use of effective leadership practices, and how their practices influence school improvement and the school’s learning climate. The authors also investigated how the frequency of effective leadership practices related to the strength of district support and the extent of school problems and student poverty. Finally, the authors examined the contribution of exemplary leade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
172
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(189 citation statements)
references
References 34 publications
5
172
0
12
Order By: Relevance
“…"Innovative" program features have been recognized as being more effective. Such features include a well-defined theory of action, a coherent curriculum in alignment with national and state standards, integration of theory and practice, and socialization and support mechanisms such as cohorts and mentoring (Orr & Orphanos, 2011).…”
Section: Content Analysis Of 2013 Spl Evaluation Proposalsmentioning
confidence: 99%
See 1 more Smart Citation
“…"Innovative" program features have been recognized as being more effective. Such features include a well-defined theory of action, a coherent curriculum in alignment with national and state standards, integration of theory and practice, and socialization and support mechanisms such as cohorts and mentoring (Orr & Orphanos, 2011).…”
Section: Content Analysis Of 2013 Spl Evaluation Proposalsmentioning
confidence: 99%
“…For example, Fuller, Young, and Baker (2011) and Orr and Orphanos (2011) examined the influence of principal preparation programs on student achievement. Orr (2011) studied the program experiences and career outcomes of graduates of leadership preparation programs.…”
Section: Content Analysis Of 2013 Spl Evaluation Proposalsmentioning
confidence: 99%
“…This is important because research has shown that good leadership is associated with improvement for organizations (Orr & Orphanos, 2011) and also -and indirectly -and also with student achievement to some extent (Bhengu & Mkhize, 2013).…”
Section: Mireia Tintorémentioning
confidence: 99%
“…These programmes are intended to direct and support the transitions of classroom teachers and other educational professionals into leadership roles and support the development of skills and habits of mind beyond those that leadership candidates might pick up in their day-to-day job experience (Browne-Ferrigno and Muth 2004; Karanxha and Agosto 2012;Nevarez and Wood 2007;Orr and Orphanos 2011).…”
Section: Literature Reviewmentioning
confidence: 99%